1997
DOI: 10.1177/107808749703200502
|View full text |Cite
|
Sign up to set email alerts
|

The Issue of Governance in Neighborhood-Based Initiatives

Abstract: The authors of this issue-mapping article explore the rationale behind, and issues bearing on, the governance of community-based initiatives. They examine three issues relevant to the formation of local governance structures: the relationship between neighborhood-based governance structures and local government; issues of representation, legitimacy, and connection; and long-term viability. They suggest an agenda for further exploration that includes examining the relative benefits of different governance struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 10 publications
0
34
0
Order By: Relevance
“…Thinking can become more practical through collaboration as well. Partnerships that bring academics and health professionals together with the people most affected by health problems have the potential to produce more grounded, locally responsive theories and strategies that link science to local experiences and resources (Chaskin and Garg 1997;Israel et al 1998;Potapchuk, Crocker, and Schechter 1999;Richardson and Allegrante 2000). Finally, collaborative thinking has been described as transformative.…”
Section: Synergy: the Unique Advantage Of Collaborationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thinking can become more practical through collaboration as well. Partnerships that bring academics and health professionals together with the people most affected by health problems have the potential to produce more grounded, locally responsive theories and strategies that link science to local experiences and resources (Chaskin and Garg 1997;Israel et al 1998;Potapchuk, Crocker, and Schechter 1999;Richardson and Allegrante 2000). Finally, collaborative thinking has been described as transformative.…”
Section: Synergy: the Unique Advantage Of Collaborationmentioning
confidence: 99%
“…Of the many administrative and management functions that have been discussed in the literature (Chaskin and Garg 1997;Israel et al 1998;Lasker et al 1997;Mitchell and Shortell 2000;Selin and Myers 1995;Together We Can 1998;Waddock and Bannister 1991;Wandersman, Goodman, and Butterfoss 1997), several are likely to be important determinants of partnership synergy. For example, extensive outreach, orientation, and logistical supports are needed to enable a broad range of community residents and organizations to participate meaningfully in the partnership's work, which is a prerequisite for achieving high levels of partnership synergy.…”
Section: Determinants Of Partnership Synergymentioning
confidence: 99%
“…It was found that the scale varied from a social unit, a spatial unit or a network of relationships and the associations and patterns of uses [26]. Park and Rogers also identified the difficulties of selecting the right scale of neighborhood through a review of planning theory, guideline and empirical research [27].…”
Section: Neighborhood Concept and Neighborhood Planningmentioning
confidence: 99%
“…Nevertheless, the extent, the outcomes, and the methodologies with which urban selforganization can be managed are largely debated (Bond and Thompson-Fawcett, 2007;Campbell and Marshall, 2000;Innes and Booher, 2004;Van Meerkerk et al, 2013). Chaskin and Garg (1997), Chaskin (2003), Chaskin et al (2012), Hasanov and Beaumont (2016), Lepofsky andFraser (2003), andMartin (2004) consider the challenges to put into action urban initiatives from non-governmental actors. Edelenbos (2005), Healey (2006), Kathi and Cooper (2005), Smith (2010) examine the difficulties of making effective collaborations with local administrations or agencies to pledge the implementation.…”
Section: Self-organization In Urban Interventionsmentioning
confidence: 99%